How an economy grows and why it crashes - Schiff, Peter D., 1963-; Schiff, Andrew; Leach, Brendan (Hoboken, New Jersey : Wiley, 2014)
Offers straight answers to every question you've ever had about how the economy works and how it affects your life. This title starts with three guys on an island who barely survive by fishing barehanded.
An idea is born -- Sharing the wealth -- The many uses of credit -- Economic expansion.
Includes index.
"Based on Irwin Schiff's book, How an Economy Grows and Why It Doesn't, which was published by Freedom Books in 1985."
rua 23/06/15
Loans
Keywords: Business cycles; Financial crises; Economic development